Two novel testis-specific long noncoding RNAs produced by 1700121C10Rik are dispensable for male fertility in mice - Chaojie LI; Chunling SHEN; Xuan SHANG; Lingyun TANG; Wenfeng XIONG; Haoyang GE; Hongxin ZHANG; Shunyuan LU; Yan SHEN; Jinjin WANG; Jian FEI; Zhugang WANG (The Society for Reproduction and Development, 2019)
Testis-specific genes are prone to affect spermatogenesis or sperm fertility, and thus may play pivotal roles in male reproduction. However, whether a gene really affects male reproduction in vivo needs to be confirmed using a gene knock-out (KO) model, a 'gold standard' method. Increasing studies have found that some of the evolutionarily conserved testis-enriched genes are not essential for male fertility. In this study, we report that 1700121C10Rik, a previously uncharacterized gene, is specifically expressed in the testis and produces two long noncoding RNAs (lncRNAs) in mouse: Transcript 1 and Transcript 2. qRT-PCR, northern blotting, and in situ hybridization revealed that expression of both the lncRNAs commenced at the onset of sexual maturity and was predominant in round and elongating spermatids during spermiogenesis. Moreover, we found different subcellular localization of Transcript 1 and Transcript 2 that was predominant in the cytoplasm and nucleus, respectively. 1700121C10Rik-KO mouse model disrupting Transcript 1 and Transcript 2 expression was generated by CRISPR/Cas9 to determine their role in male reproduction. Results showed that 1700121C10Rik-KO male mice were fully fertile with approximately standard testis size, testicular histology, sperm production, sperm morphology, sperm motility, and induction of acrosome reaction. Thus, we conclude that both the testis-specific 1700121C10Rik-produced lncRNAs are dispensable for male fertility in mice under standard laboratory conditions.